2020
DOI: 10.1007/s00203-020-02041-4
|View full text |Cite
|
Sign up to set email alerts
|

The mechanisms underlying antigenic variation and maintenance of genomic integrity in Mycoplasma pneumoniae and Mycoplasma genitalium

Abstract: Mycoplasma pneumoniae and Mycoplasma genitalium are important causative agents of infections in humans. Like all other mycoplasmas, these species possess genomes that are significantly smaller than that of other prokaryotes. Moreover, both organisms possess an exceptionally compact set of DNA recombination and repair-associated genes. These genes, however, are sufficient to generate antigenic variation by means of homologous recombination between specific repetitive genomic elements. At the same time, these my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 102 publications
(154 reference statements)
0
7
0
Order By: Relevance
“…Interestingly, by contrast with p1 type 1, more variant strains have been characterized among type 2. This might be attributed to type-specific differences in the functionality of proteins putatively involved in DNA recombination and repair in M. pneumoniae and M. genitalium ( Sluijter et al, 2010 ; Hakim et al, 2021 ).…”
Section: Evaluation Of Common Typing Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, by contrast with p1 type 1, more variant strains have been characterized among type 2. This might be attributed to type-specific differences in the functionality of proteins putatively involved in DNA recombination and repair in M. pneumoniae and M. genitalium ( Sluijter et al, 2010 ; Hakim et al, 2021 ).…”
Section: Evaluation Of Common Typing Methodsmentioning
confidence: 99%
“…Four repetitive elements (RepMp1, 2/3, 4, and 5) were found in M. pneumoniae , whereas repeated sequences from M. genitalium cluster in nine discrete regions are known as MgPar. Genome parts with copies of repetitive elements can be exchanged by homologous recombination ( Musatovova et al, 2008 ; Spuesens et al, 2009 ; Hakim et al, 2021 ). This also applies to genes coding for surface-localized and antigenic proteins with special importance for the infection process such as the adhesins P1 and P40/P90 from M. pneumoniae , and MgpB and MgpC from M. genitalium (also known as P140 and P110).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MgPar is a general term for the nine repetitive DNA sequences that compose the chromosome of M. genitalium , and contains 79–90% of MgpB and MgpC gene homology sequences ( Fraser et al, 1995 ). Since MgPar sequences have only partial and incomplete copies of MgpB and/or MgpC , which are homologous to different regions of these two genes, such homologous but not identical MgPar sequences are recombined into MgpB or MgpC , resulting in the expression of variant MgPa and P110 proteins, causing genome heterogeneity of M. genitalium ( Iverson-Cabral et al, 2007 ; Hakim et al, 2021 ). The antigenic variation of these proteins can not only optimize adhesion, but also help to avoid host immune response and promote persistence, which plays a key role in the pathogenicity of M. genitalium and escape from the host immune system, and is essential for the survival of M. genitalium ( Taylor-Robinson and Jensen, 2011 ).…”
Section: Molecular Pathogenic Characteristics Of Mycoplasma...mentioning
confidence: 99%
“…In spite of limited size, the genomes of M. pneumoniae consist of a significant portion of repeated elements, which are dispersed throughout the genome and constitute approximately 8% of the genome. It has been demonstrated that these genes are sufficient to generate antigenic variation by homologous recombination between specific repetitive genomic elements [29] (Fig. 1d).…”
Section: Antigen Polymorphism and Variationmentioning
confidence: 99%